Managing the high-producing herd. III. Producing high quality milk - Shirley, John E. (Kansas Agricultural Experiment Station, 2012)
Progress in the dairy industry over the past 30 yr can be defined as a movement toward fewer farms, more cows per farm, fewer total cows, more milk per cow, a gradual decline in total annual milk production from 1950 through 1975 followed by a sharp increase through 1985, a decrease in per capita consumption, and an increase in milk quality.
Keywords: Dairy; Milk; Milk production